Space Weather Bibliometrics for 2022: Going Beyond Impact Factor - Noé Lugaz (Space Weather)
Abstract I discuss the impact factor of Space Weather for 2021, its small decrease with respect to the number in 2020, and potential causes for this decrease. The limitations of the impact factor are emphasized as reported in past studies, in particular due to the large weight of highly cited papers. For Space Weather, over several years, the median number of citations received by a paper per year is close to the impact factor at the time of publication, with very few papers receiving no citations. I expect that, as the solar cycle ramps up, the impact factor will start to grow again.